Réponses

2014-06-02T15:38:19+02:00
1) A = (-3x+6)(7x-4)-(-3x+6)(x-5)
  =  -3x × 7x -3x × (-4) + 6 × 7x + 6×4 +3x × x +3x × (-5) - 6 × x - 6 × 5
  = -21x² +12x + 42x + 24 + 3x² -15x -6x -30
  = -18x² + 33x -6

2)  A = (-3x+6)(7x-4)-(-3x+6)(x-5)
         = (-3x+6)[(7x-4)-(x-5)]
         =  (-3x+6)(7x-4-x+5)
         = (-3x+6)(6x+1)

3)  A = (-3×(-2)+6)(7×(-2)-4)-(-3×(-2)+6)(-2-5)
         = 12×(-18)+12×(-7)
         = -132

pour le 3) je suis pas sur que c'est juste
C'est pas 7x+4 c'est 7x-4
haa oui ta raison
2014-06-02T16:44:37+02:00
1) A=(-3x+6)(7x-4)-(-3x+6)(x-5)
A=-21x²+12x+42x-24-(3x²+15x+6x-30)
A=-21x²+3x²+54x-21x-24+30
A=-18x²+33x+6

2) A=(-3x+6)[(7x-4)-(x-5)]
A=(-3x+6)(6x+1)

3) Si x=-2 ⇒ A=(-3*(-2)+6)(6*(-2)+1)
A=12*(-11)=-132